2010
DOI: 10.1002/pssa.201000509
|View full text |Cite
|
Sign up to set email alerts
|

Microwave performance of ZnO/ZnMgO heterostructure field effect transistors

Abstract: We report the first microwave performance of single crystalline ZnO/ZnMgO heterostructure field‐effect transistors (HFETs). The structure consisted of a 15‐nm‐thick ZnO channel layer was grown by molecular beam epitaxy (MBE) on an a‐sapphire substrate. Two‐finger type HFETs with 1 or 2‐µm‐long gate were fabricated and measured for microwave performance. The transconductance of the HFETs are 28 and 23 mS/mm for 1 and 2‐µm‐gate devices, respectively. The microwave measurement of ZnO‐based TFTs revealed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 16 publications
2
29
2
Order By: Relevance
“…C ZnO is a prime candidate for next generation opto-and microelectronics with a large exciton binding energy that permits efficient light emission at room temperature. [1][2][3] The 3.37 eV band gap of ZnO can be tuned by incorporating either Mg or Cd 4 to enable complex heterostructures that can enhance transport properties in ZnO based transistors 5,6 and optoelectronic efficiency of UV lasers, 7 light emitting diodes, and solar blind detectors. 8 The ZnO band gap increases with Mg alloying and Mg can be incorporated into ZnO at low concentrations without significantly disrupting the wurtzite structure.…”
mentioning
confidence: 99%
“…C ZnO is a prime candidate for next generation opto-and microelectronics with a large exciton binding energy that permits efficient light emission at room temperature. [1][2][3] The 3.37 eV band gap of ZnO can be tuned by incorporating either Mg or Cd 4 to enable complex heterostructures that can enhance transport properties in ZnO based transistors 5,6 and optoelectronic efficiency of UV lasers, 7 light emitting diodes, and solar blind detectors. 8 The ZnO band gap increases with Mg alloying and Mg can be incorporated into ZnO at low concentrations without significantly disrupting the wurtzite structure.…”
mentioning
confidence: 99%
“…The transfer curve suggests a subthreshold slope (SS), a saturation mobility (l sat ), a maximum transconductance (g m ), a current on-off ratio, and a threshold voltage (V th ) of 0.29 V/decade, 12.7 cm 2 /V s, 6.3 mS/mm, 1.4 Â 10 6 , 0.27 V, respectively. Typically a higher g m is obtained for a depletion mode device due to its higher carrier density [8][9][10][11]. However, enhancement mode operation is more desired for many applications due to less power consumption.…”
Section: Device Characterizationsmentioning
confidence: 98%
“…In addition, our device exhibits a f max /f T ratio as high as 2.8, which is mainly attributed to the high drain current and the low drain output conductance [21]. To evaluate the high-speed capability of a-IGZO, saturation velocity (v s ) was estimated following the relationship f T = v s /2pL G [10]. A saturation velocity v s of 3.8 Â 10 5 cm/s is obtained.…”
Section: Device Characterizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14] Particularly, the application to high frequency devices has attracted significant attentions these years. 15 For high frequency working applications, detailed investigations on the electron transport properties in Zn 1−x Mg x O are required, especially on the transient electron transport characteristics. Up to date, only limited studies have been reported on the steady-state electron transport properties of Zn 1−x Mg x O.…”
Section: Introductionmentioning
confidence: 99%